Catabolism in Critical Illness: A Reanalysis of the REducing Deaths due to OXidative Stress (REDOXS) Trial*. Issue 7 (28th February 2022) - Haines, Ryan W.; Fowler, Alexander J.; Wan, Yize I.; Flower, Luke; Heyland, Daren K.; Day, Andrew; Pearse, Rupert M.; Prowle, John R.; Puthucheary, Zudin
Abstract : OBJECTIVES: Ongoing risk of death and poor functional outcomes are important consequences of prolonged critical illness. Characterizing the catabolic phenotype of prolonged critical illness could illuminate biological processes and inform strategies to attenuate catabolism. We aimed to examine if urea-to-creatinine ratio, a catabolic signature of prolonged critical illness, was associated with mortality after the first week of ICU stay. DESIGN: Reanalysis of multicenter randomized trial of glutamine supplementation in critical illness (REducing Deaths due to OXidative Stress [REDOXS]). SETTING: Multiple adult ICUs. PATIENTS: Adult patients admitted to ICU with two or more organ failures related to their acute illness and surviving to day 7. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: The association between time-varying urea-to-creatinine ratio and 30-day mortality was tested using Bayesian joint models adjusted for prespecified-covariates (age, kidney replacement therapy, baseline Sequential Organ Failure Assessment, dietary protein [g/kg/d], kidney dysfunction, and glutamine-randomization). From 1, 021 patients surviving to day 7, 166 (16.3%) died by day 30. After adjustment in a joint model, a higher time-varying urea-to-creatinine ratio was associated with increased mortality (hazard ratio [HR], 2.15; 95% credible interval, 1.66–2.82, for a two-fold greater urea-to-creatinine ratio). This association persisted throughout the 30-day follow-up. Mediation analysis was performed to explore urea-to-creatinine ratio as a mediator-variable for the increased risk of death reported in REDOXS when randomized to glutamine, an exogenous nitrogen load. Urea-to-creatinine ratio closest to day 7 was estimated to mediate the risk of death associated with randomization to glutamine supplementation (HR, 1.20; 95% CI, 1.04–1.38; p = 0.014), with no evidence of a direct effect of glutamine (HR, 0.90; 95% CI, 0.62–1.30; p = 0.566). CONCLUSIONS: The catabolic phenotype measured by increased urea-to-creatinine ratio is associated with increased risk of death during prolonged ICU stay and signals the deleterious effects of glutamine administration in the REDOXS study. Urea-to-creatinine ratio is a promising catabolic signature and potential interventional target.